Robust fitting of mixture of factor analyzers using the trimmed likelihood estimator - Yang, Li (Kansas State University, 2014)
Mixtures of factor analyzers have been popularly used to cluster the high dimensional data. However, the traditional estimation method is based on the normality assumptions of random terms and thus is sensitive to outliers. In this article, we introduce a robust estimation procedure of mixtures of factor analyzers using the trimmed likelihood estimator (TLE). We use a simulation study and a real data application to demonstrate the robustness of the trimmed estimation procedure and compare it with the traditional normality based maximum likelihood estimate.
Keywords: EM algorithm; Factor analysis; Mixture models; Robustness; Trimmed likelihood estimator; Statistics (0463)